Assessment, Characterization, and Bioprocessing of E-Waste Plastics in the Environment - Bakare-Abidola, Taiwo; Olaoye, Jelil (Asian Journal of Science, Technology, Engineering, and Art, 2025)
E-waste plastics pose significant environmental and health challenges due to their complex composition and the harmful chemicals they contain. The improper disposal of these materials through methods like landfilling and incineration exacerbates their environmental impact. This review explores the assessment, characterization, and bioprocessing of e-waste plastics, focusing on their chemical properties, degradation mechanisms, and potential biotechnological solutions. Emerging technologies such as microbial degradation and enzymatic breakdown offer promising alternatives for the efficient recycling of these materials, potentially reducing their environmental footprint. The integration of these biotechnological approaches within circular economy models could provide a sustainable solution for managing plastic waste. However, challenges related to scalability, toxicity, and the economic viability of these solutions remain. Additionally, effective policy frameworks and regulations are crucial in guiding the sustainable management of e-waste plastics. This review also discusses future research directions, emphasizing the need for optimized bioremediation techniques and the importance of strengthening international policies to address the growing issue of e-waste plastics.